Asset based revenue driven digital incubation (ARDI) for MSME financing: A scenario-based simulation of pawn based lending at pawnshop - Muhammad Raffi Aditya Pradipta; Nabila Farah Faradina (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Pawn-based financing has played a critical role in improving MSME liquidity access in Indonesia, particularly through Pegadaian. However, its function remains largely transactional, positioning Pegadaian primarily as a short-term liquidity provider rather than a growth-oriented financing engine. This structural limitation constrains MSME business continuity, performance development, and long-term financial inclusion. Methods: This study proposes Asset Based Revenue Driven Digital Incubation (ARDI) as a reconfiguration of pawn-based MSME financing that integrates asset-based access, revenue-linked repayment, and digital performance monitoring. Using a scenario-based simulation approach, the study evaluates MSME-level, institutional-level, and system-level outcomes under a baseline pawn-based financing configuration and an ARDI scenario. Simulation parameters are derived from literature-consistent risk adjustments and institutional data patterns. Findings: At the MSME level, ARDI improves revenue performance, business survival probability, and financing continuity by aligning repayment obligations with cash-flow capacity. At the institutional level, Pegadaian experiences lower non-performing pawn ratios and reduced loss severity, indicating enhanced portfolio stability. When aggregated at the system level, these improvements translate into stronger financial inclusion, improved MSME bankability, and increased efficiency through digital integration, suggesting a reduced constraint on sustainable MSME financing capacity. Conclusion: The results demonstrate that the limitations of pawn-based MSME financing are not rooted in access constraints, but in the absence of performance linkage, adaptive repayment mechanisms, and data-driven monitoring. ARDI addresses these gaps by transforming pawn-based financing from a liquidity instrument into a structured incubation pathway that supports MSME development while maintaining institutional prudence. Novelty/Originality of this article: This study introduces ARDI as a novel framework that bridges asset-based lending and revenue-driven incubation within a pawn-based institutional context, offering a scalable and policy-relevant pathway to strengthen MSME financing ecosystems.